Collembola Communities, 20 Years After the Establishment of Distinct Revegetation Treatments in a Severely Eroded Area in South Iceland - Kapinga, Esther; Óskarsson, Hlynur; Halldórsson, Guðmundur; Sturludóttir, Erla; Holmstrup, Martin (Studia Ecologiae et Bioethicae, 2022)
Several restoration methods have been developed to aid ecosystem development from highly degraded Icelandic deserts into fully vegetated functional ecosystems. Despite the critical role of soil biota in many key ecosystem processes, the effect of restoration efforts on soil biota has rarely been explored. We took advantage of a large-scale restoration field experiment, to study the effect of distinct revegetation treatments on the taxonomic and functional composition of Collembola communities. Soil samples were taken from plots (one ha. each), that had received functionally distinct revegetation treatments; i: grass + fertilizer, ii: birch seedlings, iii: willow cuttings, iv: lupine and v: control. We were able to show that different revegetation treatments led to the establishment of distinct collembola communities in terms of density and taxonomic and functional composition, 20 years after the revegetation process had started. Life-forms were responsive to revegetation treatment, which suggests that the treatments had induced successional trajectories that lead to distinct habitat conditions, especially with respect to abiotic stress. In contrast to literature, eu-edaphic species were dominating in plots, which were exposed to high levels of disturbance and fluctuations in abiotic conditions. Further research is needed to unravel, to which extent resource supply and abiotic habitat conditions steer Collembola community development across successional trajectories.